Estratégias de operações de propriedades produtoras de grãos do Núcleo Oeste de Mato Grosso - Leitner, Camyla Piran Stiegler (Universidade Federal de São Carlos, 2015)
The operation strategy is responsible for key decisions of activities to be perform by the function of production, in order to achieve competitive advantage in the market. Therefore, studies on the operations strategy are recurring in the industrial and service sectors. Agribusiness is the primary responsible for good Brazilian economic results, mainly by export the grains produced by rural enterprises throughout the country, especially in Mato Grosso State. However, there is little research about management of farms, even less for the studies on competitive positioning and performance of these enterprises regarding operation strategy. Thus, this research aimed to identify and analyze strategic groups of grain farms established in the Mato Grosso State West Center counties regarding the operations strategy issues. Therefore, a cross-sectional survey-study was design directed to the farmers from the APROSOJA West Region. Data were collected using a structured questionnaire with questions about the farm profile, competitive priorities and structural and infrastructural decisions of producers on grain production. The responses obtained, 104 from the 1020 farms registered in the West Region, had a return rate of 10%. Data analyses were carried out using descriptive statistics and multivariate analysis methods. Descriptive analysis showed the main farm characteristics (location, size, employee number, main products, diversification, etc.), the target markets and their factors (main customers, certifications, marketing forms). These issues enables to identify the competitive strategy of the surveyed farms. Factorial analysis has provided verification of the constructs latent factors, which forms the operations strategy content - competitive priorities and structural and infrastructural decisions. These factors showed the variables that best explains the constructs to this research context and are useful as input to a third analysis, which proposed the formation of strategic groups. Using cluster analysis, strategic groups were formed from the latent factors of Operation and competitive strategy variables. Results indicate very similar competitive priorities characteristics; however, investments in structural and infrastructural decisions apparently have allowed a better performance to the farms. The main theoretical contribution of this work for operations strategy is the research of this concept in an agricultural context, where it was possible to identify latent factors components and to understand how the strategic decisions coherence for operations, also in this segment, enables positive result achievements to farm companies.
Keywords: Organização da produção; Agroindústria; Semiformação; Taxonomia; Survey; Productive operations; Agribusiness; Taxonomy; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO